SOMATOFORM AND DISSOCIATIVE EXPERIENCES REPORTED AMONG POSTGRADUATE NURSING STUDENTS AND IT’S RELATION WITH THEIR SLEEP QUALITY - Libina Babu; Bincy Kurien; Binu Paul; JB Bivin (Indian Journal of Psychiatric Nursing)
The present study was aimed at assessing the somatoform and dissociative experiences reported among postgraduate (PG) nursing students and to correlate it with their sleep quality. A descriptive research design with cross-sectional measurement was used. Data was collected from randomly selected PG nursing students (n=100) using standardized instruments such as Somatoform Dissociation Questionnaire 20 (SDQ 20) and Pittsburgh Sleep Quality Index (PSQI). Analysis revealed that 5.22% students had somatoform and dissociative experiences and 52.24% had poor sleep quality. There indicated a significant positive correlation (r=0.45, p<0.01) between somatoform and dissociation experiences and sleep quality of PG nursing students. The promotion of sleep hygiene among student nurses would be beneficial for their psychological welfare.